Optimized Organosolv Pretreatment of Biomass Residues Using 2-Methyltetrahydrofuran and n-Butanol - Egidio Viola (MDPI AG, 2021)
Wheat straw and eucalyptus residues were pretreated in a biphasic system, constituted of butanol (n-butanol) or 2-methyltetrahydrofuran (2M-THF) and aqueous oxalic acid solutions. The pretreatments were carried out in a 300 mL Parr reactor (Autoclave Buchi Limbo-li®) with a solid load of 5 wt.%, the temperature in the range 140–180 °C, oxalic acid load from 0 to 10 wt.% and a duration of 30–90 min. The obtained slurry was then fractionated in three streams: the aqueous phase which contained solubilized hemicellulose, the organic phase which contained the solvated lignin, and the solid residue which contained cellulose. The solid was hydrolyzed using a commercial mix of enzymes to assess cellulose digestibility and glucose production. The pretreatment was optimized to maximize the purity of the cellulose and hemicellulose fractions and the glucose recovery as free sugar. The optimization was done by using an experimental design and response surface methodology. The mass flow details of the four optimized processes were obtained. In terms of biomass fractionation, butanol demonstrated significant advantages over 2M-THF in the same range of process conditions as shown by the recovery yield of free glucose which reached 98% of the theoretical value with butanol but was 67% with 2M-THF. Tests at low temperature and low enzyme loading highlighted the importance of the solvent choice over the operating conditions. 2M-THF showed interesting performances only in the delignification step, with 90% efficiency for the straw. Regarding the use of different feedstock, fractionation and recovery were generally higher for wheat straw than for eucalyptus wood residues.